Playing with the Book : Victorian Movable Picture Books and the Child Reader - Field, Hannah, 1984- (Book collections on Project MUSE., 2019)
"Playing with the Book analyzes novelty and movable publications for young children published from 1835 to 1914, specifically the panorama fold-out, the pop-up book, the dissolving-view book, and the mechanical book. Through the analysis of these unusual texts, Field encourages a reexamination of the relationship between pictures, words, and material format."--Provided by publisher.